Peran Kualitas Pelayanan dan Suasana Toko dalam Meningkatkan Keputusan Pembelian - Aang Curatman; Yono Maulana Maulana; Ihza Mahendra (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
The increasing number of products offered by stores makes consumers more observant in making purchases, so that consumers consider before making a purchase. This has an impact on Distro B Kuningan consumers, based on the survey results obtained several symptoms of consumer purchasing decisions, including a decrease in the number of sales and a decrease in the number of buyers in 2019 and 2020. This study aims to determine the effect of the store atmosphere on purchasing decisions, to determine the effect of service quality on purchasing decisions, as well as knowing the effect of store atmosphere and service quality on purchasing decisions. This type of research is explanatory with a quantitative approach and survey methods. The results showed that there was a positive and significant influence of service quality on purchasing decisions, there was a positive and significant influence of store atmosphere on purchasing decisions, and there was a positive and significant influence of store atmosphere and service quality on purchasing decisions. Based on the results of the research, it was recommended that Distro B Kuningan pay attention to and improve the shop atmosphere to make it more attractive, and improve the quality of service delivered to customers.